The effect of argatroban on early neurological deterioration and outcomes in minor ischemic stroke: preliminary findings - Jin, Xuehong; Li, Xia; Zhang, Hong; Yao, Xiaohan; Gu, Yongquan; Pei, Shaofang; Hu, Lan (Frontiers in Neurology, 2024)
Background Minor ischemic stroke (MIS) is associated with early neurological deterioration (END) and poor prognosis. Here, we investigated whether argatroban administration can mitigate MIS-associated END and improve functional outcomes by monitoring activated partial thrombin time (APTT). Methods Data were collected for patients with MIS admitted to our hospital from January 2019 to December 2022. Patients were divided into a dual antiplatelet therapy (DAPT) group (aspirin + clopidogrel) and an argatroban group (aspirin + argatroban). Those in the latter group who achieved a target APTT of 1.5–3-fold that of baseline and <100 s at 2 h after argatroban infusion were included in the argatroban subgroup. The primary outcome was the END rate of the DAPT group versus that of the argatroban group or the argatroban subgroup. Secondary outcomes included the proportion of patients with modified Rankin Scale (mRS) 0–2 at 7 and 90 days. In addition, baseline date were compared between patients with and without END in the argatroban group. Results 363 patients were included in the DAPT group and 270 in the argatroban group. There were no significant differences in any above outcome between them. 207 pairs were included in the DAPT group and the argatroban subgroup after 1:1 propensity score matching (PSM). Significant differences were observed in the proportion of END (OR, 2.337; 95% CI, 1.200–4.550, p = 0.011) and mRS 0–2 at 7 days (OR, 0.624; 95% CI, 0.415–0.939, p = 0.023), but not in mRS 0–2 at 90 days or the hemorrhagic events between the two groups. In the argatroban group, univariate analysis showed that the rate of diabetes (OR, 2.316; 95% CI, 1.107–4.482, p = 0.023), initial random blood glucose (OR, 1.235; 95% CI, 1.070–1.425, p = 0.004), drinking history (OR, 0.445; 95% CI, 0.210–0.940, p = 0.031) or those reaching the target APTT (OR, 0.418; 95% CI, 0.184–0.949, p = 0.033) was significantly different among patients with and without END. However, there were no statistical differences in these parameters between them following multivariate analysis. Conclusion In patients with MIS, argatroban administration and reaching the target APTT can reduce the incidence of END and improve short-term functional prognosis.